First report of Exserohilum rostratum as pathogen of rice brown spot in Malaysia - Mahmad Toher, Ainu Shahirah; Mior Ahmad, Zainal Abidin; Wong, Mui Yun (American Phytopathological Society, 2016)
Leaves with brown spot symptoms were sampled from rice planting areas in the Malaysian peninsula, including Kelantan, Penang, Kedah, Perak, and Selangor, over the planting season from November 2012 to December 2013. The disease was observed on the glumes and leaves of rice plants. Mature lesions were brown with a gray or whitish centre, whereas younger lesions were small, circular, and dark brown or purplish brown. Thirteen isolates were recovered from 100 diseased leaf samples that were plated on PDA medium. The mycelia were white in early stages but after 3 to 4 days, they turned gray or dark gray. Based on morphological characteristics, molecular data (polymerase chain reaction assay and nucleotide sequence analysis) and pathogenicity tests, the causal agent was identified as Exserohilum rostratum [Setosphaeria rostrata]. This is thought to be the first report of E. rostratum as pathogen of rice brown spot in Malaysia.